Utility of Social Media for Recruitment by Orthopaedic Surgery Residency Programs. Issue 3 (July 2021) - Malyavko, Alisa; Kim, Yumin; Harmon, Tara G.; Quan, Theodore; Gu, Alex; Bernstein, Simone A.; Tabaie, Sean A.; Thakkar, Savyasachi
Abstract : Background: As the use of social media continues to rise, the presence of social media accounts among orthopaedic surgery residency programs can foster connections with other specialties, highlight departmental achievements, and be a resource for applicants to learn more about the program. This study evaluated the current utility and landscape of social media, with an emphasis on the use of Instagram, in orthopaedic surgery residency programs in the United States. Methods: A cross-sectional study of orthopaedic surgery residency Instagram accounts was performed. The Instagram accounts were evaluated for the number of followers, number of accounts following, and number of posts. Instagram posts were further categorized into academic, departmental, education, and COVID-19–related content. In addition, a search was performed to identify the presence of Twitter and Facebook accounts among orthopaedic surgery residency programs. Bivariate and multivariable logistic regression models were used to analyze the data in this study. Results: Of the 192 orthopaedic surgery residency programs evaluated, 108 programs (56%) had an Instagram account, 65 programs (34%) had a Twitter account, and 58 programs (30%) had a Facebook account. Of the 108 programs with an Instagram account, 92 accounts (85%) were created in 2020. A higher Doximity ranking of a program was positively associated with the presence of an Instagram account (p < 0.001). A significant correlation was found between the number of posts and the Instagram engagement score (p = 0.018). The majority of Instagram posts contained departmental content (54%) followed by social (13%) and COVID-19–related (10%) content. Conclusions: The presence of orthopaedic surgery residency programs on social media has grown significantly in the year 2020. With the presence of more than 50% of residency programs on Instagram, this can be a useful resource for prospective applicants and other healthcare professionals to gain insight into the activities of orthopaedic surgery residency programs across the United States.